2021
DOI: 10.3390/jof7060447
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Digestive Microbiota, Rumen Fermentations and Oxidative Stress around Parturition Are Alleviated by Live Yeast Feed Supplementation to Gestating Ewes

Abstract: Background: In ruminants, physiological and nutritional changes occur peripartum. We investigated if gastro-intestinal microbiota, rumen metabolism and antioxidant status were affected around parturition and what could be the impact of a daily supplementation of a live yeast additive in late gestating ewes. Methods: Rumen, feces and blood samples were collected from 2 groups of 14 ewes one month and a few days before parturition, and 2 weeks postpartum. Results: In the control ewes close to parturition, slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…According to this hypothesis, the ruminal microbial modifications expected with SC supplementation might impact lower gut microbiota, as suggested by studies of Bach et al ( 26 , 27 ) and thus might modulate this possible microbial transfer into the mammary gland. Live yeast supplementation leads to positive impacts on rumen microbiota and health but can also exert beneficial effects beyond the rumen on oxidative status and performance ( 26 , 31 , 96 , 97 ) , strengthening the systemic effect hypothesis. Further investigations are required to understand how SC supplementation could induce modifications in colostrum bioactive molecules and bacterial populations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to this hypothesis, the ruminal microbial modifications expected with SC supplementation might impact lower gut microbiota, as suggested by studies of Bach et al ( 26 , 27 ) and thus might modulate this possible microbial transfer into the mammary gland. Live yeast supplementation leads to positive impacts on rumen microbiota and health but can also exert beneficial effects beyond the rumen on oxidative status and performance ( 26 , 31 , 96 , 97 ) , strengthening the systemic effect hypothesis. Further investigations are required to understand how SC supplementation could induce modifications in colostrum bioactive molecules and bacterial populations.…”
Section: Discussionmentioning
confidence: 92%
“…Colostrum quality is impacted by the health condition of the gestating animal ( 28 30 ) . Probiotic supplementation peripartum could thus be a nutritional strategy to reinforce rumen functions through the stabilisation of microbial populations, leading to an enhancement of the dam's health before parturition ( 26 , 27 , 31 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the results of rumen fermentation and pH, AOC did not affect the rumen bacterial diversity, which indicated that the rumen microbial flora maintains a better steady- state after AOC supplementation. Other study reported that the rumen bacterial community was changed after feeding with DFMs ( 31 ). The inconsistent results among studies were likely due to differences in diet treatments, dietary starch contents, and experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…Strong delay in establishment of F. succinogenes was previously detected in calves or lambs separated from their dam (5,10,46). A decrease in the Fibrobacteres phylum was also observed at parturition on ewes (47), indicating that Fibrobacter may be quite sensitive to changes in the ecological conditions of the rumen. F. succinogenes is known as an important brolytic microorganism, particularly e cient in degrading recalcitrant cellulosic substrates such as straw (48,49) and also very sensitive to oxygen.…”
Section: Performance and Sanitary Status Of Mothered And Arti Cially-...mentioning
confidence: 92%